Effect of Media on Germination and Vigour of Moringa oleifera Lamk - Bahar, Nawa (Indian Forester, 2010)
The present study was conducted to find out the effect of media on germination and vigour of Moringa oleifera. The seeds of Moringa oleifera were sown in different media such as top of paper (TP), between paper (BP), sand (S) and top of sand (TS). The maximum germination per cent and high vigour index was recorded in the top of sand (TS) medium. Being a large size seed, it gave good results in sand (S) and top of paper (TP) also. It is evident from the results that the germination value of seed has little difference in both the media such as top of paper (TP) and top of sand (TS). Sand it self also proved a good medium and inexpensive other than. So, it is recommended that top of sand (TS) is good medium for testing the seed of Moringa oleifera in controlled condition.